The Dialectic of Notary Inheritance Deed Arrangement - Dinda Keumala (Universitas Airlangga, 2023)
Verifying an heir's deed of inheritance is an approach to proving an heir’s legal status. The Indonesian Ministry of Land and Special Planning Regulation No.16/2021 stipulates that a notary can make an inheritance deed for all residents in Indonesia regardless of their ethnic groups. This paper investigates the notary inheritance deed arrangement based on the regulation mentioned above and the challenges notaries still encounter in making an inheritance deed after the regulation’s enactment. The researcher applied normative research with a descriptive approach and utilized secondary data for qualitative analysis. The deductive approach to this research helped the researcher conclude that the authority of notaries to make an inheritance deed as regulated in the Indonesian Ministry of Land and Special Planning Regulation No.16/2021 contradicts their authority as regulated in the Indonesian Law on the Notary Position Act. An in-depth understanding of the customary inheritance law in all Indonesian regions challenges the authority of notaries to make an inheritance deed under the Indonesian Ministry of Land and Special Planning Regulation No. 16/2021.